1974
DOI: 10.1113/expphysiol.1974.sp002252
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Formation of Lymph Lipids in the Sheep

Abstract: 3H and 14C-labelled palmitic, stearic, oleic, linoleic and linolenic acids introduced into the duodenum of sheep were recovered in thoracic duct lymph, and the specific radioactivities of the fatty acids in the various lipid fractions were determined. Lymph fatty acids were transported mainly as triglycerides (77 %) and phospholipids ( 18%), probably mostly in the form of very low density lipoproteins rather than as chylomicrons. Lymph triglycerides transported most of the palmitic, stearic and oleic acids (74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1976
1976
1984
1984

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…115 When abnormal dietary or other experimental conditions have been imposed upon ruminant animals, changes in the flow and lipid concentration of the lymph within the intestinal and thoracic ducts have been demonstrated. 175 This feature has, indeed, been confirmed in sheep where analysis of thoracic lymph separated into fractions by ultracentrifugation showed that 73% of the lipid present was associated with the VLDL fraction and only 27% with the chylomicrons. 115 ' 130 ' 132 As in non-ruminant animals, lactation and other changes in the physiological status of the animal also influence lymphatic circulation.…”
Section: Lymphmentioning
confidence: 75%
See 2 more Smart Citations
“…115 When abnormal dietary or other experimental conditions have been imposed upon ruminant animals, changes in the flow and lipid concentration of the lymph within the intestinal and thoracic ducts have been demonstrated. 175 This feature has, indeed, been confirmed in sheep where analysis of thoracic lymph separated into fractions by ultracentrifugation showed that 73% of the lipid present was associated with the VLDL fraction and only 27% with the chylomicrons. 115 ' 130 ' 132 As in non-ruminant animals, lactation and other changes in the physiological status of the animal also influence lymphatic circulation.…”
Section: Lymphmentioning
confidence: 75%
“…26 ' 54 ' 254 Such enzymic activity appeared to be maximal within the mucosal cells of the duodenum and upper jejunum 26 and was accompanied by much higher glycerokinase activity than has been found in other animal species. 175 Very low specific activities were found for the fatty acids in the phosphohpids compared to the triglycérides of lymph indicating that there was very little synthesis of phosphohpids de novo by the a-glycerophosphate pathway. Although initial work 26 failed to provide unequivocal evidence for this biosynthetic pathway, subsequent investigations 54 ' 254 demonstrated the ability of both ovine and bovine jejunal cells to synthesize triglycérides by direct acylation of both 1-and 2-monoacylglycerol substrates.…”
Section: B Resynthesis Of Lipid In the Intestinal Mucosal Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…Discussion Leat and Harrison (1974) observed that ruminant lymph contained a high content of phospholipids relative to triacylglycerols. as indicated by a triacylglycerol .to phospholipid ratio of 3 .…”
Section: Distribution Of Radioactivity In Lymph Lipoproteinsmentioning
confidence: 99%
“…In ruminants, however, Leat and Harrison (1974), after observing a high level of phospholipid in lymph, suggested that in these animals lymph lipids are transported as very low density lipoproteins (VLDL) rather than chylomicrons.…”
Section: Introductionmentioning
confidence: 99%